2023
DOI: 10.1007/s42773-023-00214-0
|View full text |Cite
|
Sign up to set email alerts
|

Bio-assembled MgO-coated tea waste biochar efficiently decontaminates phosphate from water and kitchen waste fermentation liquid

Abstract: Crystal morphology of metal oxides in engineered metal-biochar composites governs the removal of phosphorus (P) from aqueous solutions. Up to our best knowledge, preparation of bio-assembled MgO-coated biochar and its application for the removal of P from solutions and kitchen waste fermentation liquids have not yet been studied. Therefore, in this study, a needle-like MgO particle coated tea waste biochar composite (MTC) was prepared through a novel biological assembly and template elimination process. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Previous studies of ours and others have found that magnesium oxide-doped biochar, made by pyrolyzing biomass impregnated with a magnesium salt, can strongly sorb phosphate. , The bound phosphate is coordinated to Mg and shows appreciable resistance to displacement by common anions and organic matter in soil pore water . In addition, we demonstrated that postpyrolysis treatment of biochar with the quaternary ammonium cationic polymer, poly­(diallyldimethylammonium) chloride (pDADMAC), is capable of strongly sorbing phosphate via anion exchange.…”
Section: Introductionmentioning
confidence: 58%
“…Previous studies of ours and others have found that magnesium oxide-doped biochar, made by pyrolyzing biomass impregnated with a magnesium salt, can strongly sorb phosphate. , The bound phosphate is coordinated to Mg and shows appreciable resistance to displacement by common anions and organic matter in soil pore water . In addition, we demonstrated that postpyrolysis treatment of biochar with the quaternary ammonium cationic polymer, poly­(diallyldimethylammonium) chloride (pDADMAC), is capable of strongly sorbing phosphate via anion exchange.…”
Section: Introductionmentioning
confidence: 58%
“…On the other hand, the C-O peak intensity of Mn/Mg@MV is significantly weakened compared with that of MV, while the peak representing the metal oxide peak at Mn-O and Mg-O (482 cm −1 ) [ 23 ] is significantly enhanced, which proves the successful deposition of the metal elements Mn and Mg. This is further illustrated by the significant shift in the -OH peak [ 48 ], where Mn and Mg replaced part of the -OH and -CO functional groups and formed Mn-O and Mg-O functional groups. This suggests that Mn and Mg are not simply loaded on the surface of the biochar but are bonded through stable chemical bonds.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the common physical and chemical treatment methods for NOR and other antibiotics include membrane filtration [7,8], advanced oxidation [9,10], and adsorption [11,12]. Compared to the other two methods, the adsorption method has the advantages of being economically feasible, easily carried out, and environmentally friendly [13,14]. The adsorbent used is a major factor that affects the process of adsorption.…”
Section: Introductionmentioning
confidence: 99%